A Proposed Guide for Teaching the Responsibility Unit for Third Grade Intermediate Students in the Kingdom of Saudi Arabia in Light of the service-learning Strategy (The International Journal of Educational Sciences and Arts, 2025)
This research aims to develop a proposed guide for teaching Social Studies using the Service-Learning strategy. The research employs the Descriptive Approach. A guide was created for the "Responsibility" unit in the Social Studies curriculum for third-grade female students in Saudi Arabia during the first semester of the academic year 1447/1446H. The Guide was reviewed by a group of ten experts in curricula and teaching methods to ensure the accuracy of the objectives, correct application of the Service-Learning strategy steps, and alignment of assessments with the objectives. Following their feedback, the Guide was revised, and the reviewers' approval rate reached 98%. Consequently, the Guide was finalized. The researchers recommended distributing the Guide to teachers and providing training on the implementation of the Service-Learning strategy in Social Studies education.
Keywords: Guide; Strategy; Service Learning; Social Studies